Enhancement of thermal conductivity and tensile strength of liquid silicone rubber by three-dimensional alumina network. Issue 3 (3rd July 2019) - Zou, Zhiqiang; Wu, Wei; Wang, Yi; Wang, Liang
ABSTRACT: Rapidly increasing demands for higher integration density and stability of electronic devices embrace higher requirements for thermally conductive silicone rubber, which is promisingly used in ultra-thin components. In this work, alumina whiskers (AWs) and alumina flakes (AFs) are used to modify liquid silicone rubber (LSR) by fabricating binary (AFs/LSR) or ternary (AWs/AFs/LSR) composites. The thermal conductivity and mechanical strength of the binary and ternary composites were investigated. Thermal conductivity of the binary AFs/LSR composite (25AFs/LSR) was 0.1990 W m −1 K −1, while the thermal conductivity of the ternary AFs/AWs/LSR composite (20AFs/5AWs/LSR) was 0.2655 W m −1 K −1 . Furthermore, the tensile strength of the ternary AWs/AFs/LSR composites increased by 180.9% as compared with the binary system, increased to 7.81 MPa from 2.78 MPa due to the introduction of 1 wt% AWs. As a reason, a significant synergistic effect of AWs and AFs in the enhancement of both thermal and mechanical properties of the LSR was proved. Furthermore, the dielectric property measurements demonstrated that the ternary composites exhibited a lower dielectric constant and dielectric loss, indicating that the AWs/AFs/LSR composites were qualified to be applied in the field of electronic devices.